PENYELESAIAN KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) DI INDONESIA DAN MALAYSIA: Bankruptcy Resolution and Debt Payment Deferral (PKPU) in Indonesia and Malaysia - Nadine Aurellia Shinita; Ning Adiasih (Reformasi Hukum Trisakti, 2026)
Economic and business activities are inherently associated with the risk of debtors’ failure to fulfill their financial obligations to creditors. To address such conditions, the state provides legal instruments in the form of bankruptcy and Suspension of Debt Payment Obligations (PKPU) as collective and structured mechanisms for debt settlement. This problem on this research is how the regulation of bankruptcy and PKPU settlement processes in Indonesia and to compare them with the insolvency mechanism in Malaysia. This research employs a normative legal method using statutory and comparative law approaches. The result and conclusion findings indicate that bankruptcy in Indonesia functions as a collective mechanism to protect creditors’ interests, while PKPU serves as a preventive and rehabilitative instrument that allows debt restructuring before liquidation. From a comparative perspective, Malaysia’s insolvency system emphasizes broader judicial discretion in guiding corporate restructuring. This study concludes that strengthening the role of judges through clear and accountable judicial guidelines is essential to enhance the effectiveness of PKPU and creditor protection in Indonesia.